Implementasi Website Deteksi Phishing Link Menggunakan SSL Validation dan URL Scoring - Rusma Riansyah; Dimas Aqila Aptanta; Hafiz Aryanda; Muhammad Farhan; Ibnu Rusydi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid expansion of internet usage has led to a significant increase in cybersecurity threats, particularly phishing attacks delivered through malicious links. Phishing links are designed to imitate legitimate websites in order to deceive users and steal sensitive information. This study presents the implementation of a phishing link detection website based on SSL validation and URL scoring mechanisms. The proposed system integrates heuristic-based URL analysis with real-time SSL certificate validation obtained through the SSL handshake process. Digital certificates are verified using RSA-based digital signature verification issued by trusted Certificate Authorities (CAs). In addition, the SHA-256 hash algorithm is employed to generate certificate fingerprints and URL hashes to ensure data integrity and uniqueness. The system also evaluates HTTPS usage, domain and certificate consistency, certificate validity period, and RSA public key strength. All validation results are processed using a URL scoring system to generate a security score ranging from 0 to 100, which classifies links into safe, suspicious, or dangerous categories. Experimental results demonstrate that the proposed website is capable of effectively identifying phishing indicators and providing transparent cryptographic evidence in real time. This approach can assist users in making informed decisions and improving protection against phishing threats in web environments.